1994
DOI: 10.1109/9.284879
|View full text |Cite
|
Sign up to set email alerts
|

Computational complexity of μ calculation

Abstract: uncertainty in the framework of combinatorial complexity theory. In particular, it is proved that the p recognition problem with either pure real or mixed reaUcomplex uncertainty is NP-hard. This strongly suggests that it is fbtile to pursue exact methods for calculating p of general systems with pure real or mixed uncertainty for other than small problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
133
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(138 citation statements)
references
References 8 publications
0
133
0
1
Order By: Relevance
“…Extensive computational experience suggests that the bound is often adequate for applications in robust control [29]. This is important since the computation of µ is an NP-hard problem [5]. If µ ∆ (M ) denotes the convex upper bound of µ ∆ (M ) and M ∈ C n×n , it has been shown that the ratio g n := µ ∆ (M )/µ ∆ (M ) grows no faster than a linear function of n. In …”
Section: Theorem 21 [29]mentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive computational experience suggests that the bound is often adequate for applications in robust control [29]. This is important since the computation of µ is an NP-hard problem [5]. If µ ∆ (M ) denotes the convex upper bound of µ ∆ (M ) and M ∈ C n×n , it has been shown that the ratio g n := µ ∆ (M )/µ ∆ (M ) grows no faster than a linear function of n. In …”
Section: Theorem 21 [29]mentioning
confidence: 99%
“…Although the problem is computationally NP hard [5], [16], tight bounds have been reported in the robust control literature using exclusively convex programming techniques. In a recent work [17] tests have been developed for certifying the absence of a duality gap between the structured singular value and its convex upper bound, along with a systematic procedure for reducing the duality gap when this is non-zero.…”
Section: Introductionmentioning
confidence: 99%
“…First, it proves undecidability of a certain robust stability problem under time-varying uncertainty. In that sense, it complements negative (NP-hardness) results on the robust stability of linear systems in the presence of time-invariant uncertainty [5,16,18,21]. Second, it leads to an undecidability result for a simple class of hybrid systems.…”
Section: Introductionmentioning
confidence: 68%
“…As skew µ is a generalization of µ, the calculation of the exact value of skew µ (like µ) is NP hard [16]. It is therefore necessary to consider computationally efficient algorithms that determine upper and lower bounds on skew µ.…”
Section: Theorem 4 (Bounded Frequency Test)mentioning
confidence: 99%